Formation and stability study of some Malaysian crude oil emulsions - Zulkania, Ariany (2004)
The formation of water in crude oil emulsions is often undesirable since it causes problems in petroleum recovery and processing. Hence, the objective of this study is to investigate the crude oil emulsion characteristics and its stability using some selected Malaysian crude oil emulsion samples in order to obtain a better understanding on problems. Some crude oil emulsion samples provided by ESSO Production (M) Inc. as well as model systems consisting of pure oil, synthetic oil (tolueneldecane), and crude oil components were used in the study. Some important properties of crude oils and oilfield brines, and the effect of some physical conditions on the crude oil emulsion stability were investigated. In addition, the effect of crude oil components on emulsion formation and stability was also studied. The stability was assessed by measuring the percentage of water separation. Some physical and chemical properties of crude oils have a correlation with each other. Analysis of crude oil components showed that hydrogedcarbon (HIC) ratio of wax is higher than asphaltene. Besides, Fourier Transform Infra Red (FTIR) analysis showed that asphaltene, resin, and oil contained substantial functional groups as polar carrier and aromatic contents, which have important roles in emulsion formation and stability. This study indicated that crude oils, which have higher asphaltene content, lower resinlasphaltene (RIA) ratio, and higher wax contents, would have a stable emulsion. At 28 OC, the 0.5% (wlw) of asphaltene content in crude oil was sufficient to form a stable crude oil emulsion. Asphaltene has a significant role to enhance emulsion stability, while resin would decrease the stability. Wax and solid particles could contribute to the emulsion stability but they do not effective as much as asphaltene. Analysis of factor controlling emulsion stability using factorial design provides the mathematical model, which indicates the role of crude oil components and their interactions terms on the crude oil emulsion formation and stability.